Environmental Factors in Autism - Grabrucker, Andreas M. (Frontiers in Psychiatry, 2013)
Autism is a neurodevelopmental disorders characterized by impairments in communication and social behavior, and by repetitive behaviors. Although genetic factors might be largely responsible for the occurrence of autism they cannot fully account for all cases and it is likely that in addition to a certain combination of autism-related genes, specific environmental factors might act as risk factors triggering the development of autism. Thus, the role of environmental factors in autism is an important area of research and recent data will be discussed in this review. Interestingly, the results show that many environmental risk factors are interrelated and their identification and comparison might unveil a common scheme of alterations on a contextual as well as molecular level. For example, both, disruption in the immune system and in zinc homeostasis may affect synaptic transmission in autism. Thus, here, a model is proposed that interconnects the most important and scientifically recognized environmental factors. Moreover, similarities in how these risk factors impact synapse function are discussed and a possible influence on an already well described genetic pathway leading to the development of autism via zinc homeostasis is proposed.